1985
DOI: 10.1126/science.3975611
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytes as Carcinogens: Malignant Transformation Produced by Human Neutrophils

Abstract: In a study of the relation between chronic inflammation and carcinogenesis, C3H mouse fibroblasts of the 10T 1/2 clone 8 line (10T 1/2 cells) were exposed to human neutrophils stimulated to synthesize reactive oxygen intermediates or to a cell-free enzymatic system generating superoxide (xanthine oxidase plus hypoxanthine). After exposure, the 10T 1/2 cells were either placed in tissue culture or immediately injected into athymic nude mice. Both malignant and benign tumors developed in the mice injected with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
142
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(150 citation statements)
references
References 15 publications
6
142
0
1
Order By: Relevance
“…Chronic inflammation is an important risk factor for cancer, and oxidants generated by phagocytic cells mutate bacteria and transform cultured mammalian cells (57,58). Moreover, recent genetic epidemiological studies have found a relationship between cancer risk and a polymorphism in the promoter region of the myeloperoxidase gene.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is an important risk factor for cancer, and oxidants generated by phagocytic cells mutate bacteria and transform cultured mammalian cells (57,58). Moreover, recent genetic epidemiological studies have found a relationship between cancer risk and a polymorphism in the promoter region of the myeloperoxidase gene.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chronic in¯ammation of the skin, urinary bladder, gall bladder, stomach, esophagus, bone, etc, is associated with an increased incidence of malignancies in these tissues (Weitzman and Gordon, 1990). In addition to this well-known association between in¯ammation and human carcinogenesis, previous studies have also demonstrated that cultured mouse ®broblast cells can be transformed into malignant cells when exposed to in¯ammatory leukocytes (Weitzman et al, 1985;Nassi-Calo et al, 1989;Zimmerman and Cerutti, 1984).…”
Section: Introductionmentioning
confidence: 93%
“…Reactive oxygen species (ROS) released from polymorphonuclear leukocytes and macrophages are the factors causing DNA damage in the foci of inflammation (Cerutti and Trump, 1991). ROS induce DNA strand breaks in mouse epidermal cells (Muehlematter et al, 1988), chromosomal aberrations in Chinese hamster ovary cells (Weitberg et al, 1983), and malignant transformation of cultured mouse fibroblasts (Zimmerman and Cerutti, 1984;Weitzman et al, 1985). Previous studies have shown that ROS can also cause DNA strand breaks (Carson et al, 1986) and chromosomal aberrations (Duell et al, 1995) in resting peripheral blood lymphocytes or phytohemagglutinin-stimulated lymphocytes.…”
mentioning
confidence: 99%